## Solving the Equation (x+3)(x+4)-(x-3)(x-5)=2

This article will guide you through the steps to solve the equation **(x+3)(x+4)-(x-3)(x-5)=2**.

### Expanding the Equation

First, we need to expand the equation by multiplying out the brackets:

**(x+3)(x+4)**= x² + 7x + 12**(x-3)(x-5)**= x² - 8x + 15

Now, the equation becomes: x² + 7x + 12 - (x² - 8x + 15) = 2

### Simplifying the Equation

Next, we can simplify the equation by removing the brackets and combining like terms:

x² + 7x + 12 - x² + 8x - 15 = 2 15x - 3 = 2

### Isolating the Variable

To isolate the variable **x**, we need to move the constant term to the right side of the equation:

15x = 2 + 3 15x = 5

### Solving for x

Finally, we can solve for **x** by dividing both sides of the equation by 15:

x = 5 / 15
**x = 1/3**

### Solution

Therefore, the solution to the equation **(x+3)(x+4)-(x-3)(x-5)=2** is **x = 1/3**.